Sustainability Development-Based Agroindustry in Chemistry Learning to Improve the Preservice Chemistry Teachers’ Competence - Hasibuan, Nur Azizah Putri; Paristiowati, Maria; Erdawati, Erdawati (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research aims to integrate agroindustry and sustainability development into chemistry learning through the Project-Based Learning model (PjBL) to improve the competence of preservice chemistry teachers. This research employed the qualitative method. The Summer Course program was held collaboratively by Universitas Negeri Jakarta, Institut Pertanian Bogor, and Villanova University. The program was implemented online within six weeks due to the COVID-19 pandemic. The participants consisted of 25 students. The data had been collected through interviews, questionnaires, observations, student portfolios, and reflection journals. Based on the analysis, several projects developed by preservice chemistry teachers increased the application to solve sustainability problems in the agroindustry field. Furthermore, the project was expected to be developed into a natural product that can increase the agroindustry value for coffee farmers. The findings also foster the preservice chemistry teachers to improve their creative thinking, collaboration, higher-order thinking skills, and problem-solving skills. Besides, they developed their communication and collaboration after participating in the program. The paper outline is a project development learning experience in a sustainable field and would be a good resource for student-teacher involvement in teacher education.